A state of the art opinion mining and its application domains - Binali, Haji; Potdar, Vidyasagar; Wu, Chen (IEEE Computer Society, 2009)
This paper critically evaluates existing work, presents an opinion mining framework and exposes new areas of research in opinion mining. Individuals, businesses and government can now easily know the general opinion prevailing on a product, company or public policy. At the core of this field is semantic orientation of subjective terms in documents or reviews which seeks to establish their contextual connotation through opinion mining. Overall item sentiment can be expressed based on its sentiment words in general or by specifically identifying its features and the opinions being expressed about them. This leads us to the motivation of the framework for opinion mining and categorizing current literature in such a manner as to make clear, research opportunities. The freedom offered by the web as a platform for presenting opinions on any subject brings with it many new opportunities.